Diffuse midline glioma of the brainstem: genetic features, complications and treatment prospects - A. M. Kryanev; I. D. Rozanov; S. S. Lebedev; D. N. Grekov; K. S. Titov; T. A. Yakusheva; M. Kh. Salpagarov (Опухоли головы и шеи)
Diffuse midline glioma of the brain is a rare but very aggressive and resistant glial tumor. This pathology is characterized by impossibility of radical surgical treatment, radioresistance, resistance to drug treatment, high morbidity in children, low quality of life of the patients, frequent complications in the form of neurologic deficit, and unfavorable prognosis. The absence of effective treatment scheme for diffuse midline glioma requires identification of other methods (oncolytic virus therapy, immunotherapy) but there is not enough data on this topic leading to the necessity of its further investigation.